Evaluating The Development of Leadership Competencies of Telecommunication Project Managers : A Scenario Planning Approach - Misbahuddin; Mohammad Syamsul Maarif; Arif Imam Suroso; Yunus Triyonggo (Agregat: Jurnal Ekonomi dan Bisnis, 2025)
The future of project management in the telecommunications industry is not just a distant possibility but a rapidly approaching reality. Driven by unprecedented technological advancements and a complex project environment, this transformation is imminent. This paper explores the development of leadership competencies among project managers in this volatile landscape through a combination of transactional and transformational leadership styles in facing future challenges. Using a scenario planning methodology, the author identifies critical drivers through a PESTLE analysis. The author then employs a 2x2 matrix to categorize environments based on two key uncertainties in the telecommunications industry: project complexity and technological uncertainty. This results in a Telecommunications Project Scenario Matrix, consisting of four future scenarios, namely Stability, Complexity, Innovation, and Disruption Quadrants. These scenarios present distinct challenges and opportunities for project managers, ultimately shaping the leadership competencies required for success in combining transactional and transformational styles. The analysis suggests five leadership development actions. This insight will be valuable for academics and project management practitioners in the telecommunications industry.